Hemorrhagic Transformation in Stroke - Dianarelys Villafuerte Delgado; Odalys Yanes Isray; Félix González Pérez (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Cerebro-vascular disease is constituted by a group of severe entities which occur when blood supply to a brain zone is interrupted, caused by any anomalies as a result of a pathological process of blood vessels. Cerebro-vascular disease is associated to a high morbidity and mortality, among its complications hemorrhagic transformation occurs in a 6 % of the cases with a high mortality. Hemorrhagic transformation of stroke is one of the most fearful complications. It is presented a case of a patient with pathological antecedents of hypertension and ischemic heart disease who was admitted after having had a brain tomography without contrast which showed mild signs of diffuse cortical atrophy. In addition it was observed a hypodense zone which occupied almost the total hemisphere, reason for which it was decided to diagnose a hemorrhagic transformation of stroke.